The role of the miR-30a-5p/BCL2L11 pathway in rosmarinic acid-induced apoptosis in MDA-MB-231-derived breast cancer stem-like cells - Wang, Wei; Zhang, Yuefen; Huang, Xiaomin; Li, Dan; Lin, Qi; Zhuang, Hailin; Li, Hong (Frontiers in Pharmacology, 2024)
Background: Rosmarinic acid (RA), a natural phenolic acid, exhibits promising anti-cancer properties. The abnormal expression of microRNA (miRNA) regulates the gene expression and plays a role as an oncogenic or tumor suppressor in TNBC. However, the biological role of RA in miR-30a-5p on BCL2L11 during MDA-MB-231 induced breast cancer stem-like cells (BCSCs) progression and its regulatory mechanism have not been elucidated. Objective: To investigate whether RA inhibited the silencing effect of miR-30a-5p on the BCL2L11 gene and promoted apoptosis in BCSCs. Materials and Methods: We assessed the migration, colony formation, proliferation, cell cycle, and apoptosis of BCSCs after RA treatment using the wound-healing assay, colony formation assay, CCK-8 assay, and flow cytometry, respectively. The expression of mRNA and protein levels of BCL-2, Bax, BCL2L11, and P53 genes in BCSCs after RA treatment was obtained by real-time polymerase chain reaction and Western blot. Differential miRNA expression in BCSCs was analyzed by high-throughput sequencing. Targetscan was utilized to predict the targets of miR-30a-5p. The dual luciferase reporter system was used for validation of the miR-30a-5p target. Results: Wound-healing assay, colony formation assay, CCK-8 assay, and cell cycle assay results showed that RA inhibited migration, colony formation and viability of BCSCs, and cell cycle arrest in the G0-G1 phase. At the highest dose of RA, we noticed cell atrophy, while the arrest rate at 100 μg/mL RA surpassed that at 200 μg/mL RA. Apoptotic cells appeared early (Membrane Associated Protein V FITC+, PI-) or late (Membrane Associated Protein V FITC+, PI+) upon administration of 200 μg/mL RA, Using high-throughput sequencing to compare the differences in miRNA expression, we detected down-regulation of miR-30a-5p expression, and the results of dual luciferase reporter gene analysis indicated that BCL2L11 was a direct target of miR-30a-5p. Conclusion: RA inhibited the silencing effect of miR-30a-5p on the BCL2L11 gene and enhanced apoptosis in BCSCs.